Cross and Roman legion: popular imaginary in the first century (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2018)
From the year 63 BCE the new imperial order arrives in Palestine. An empire desired by the gods and considered eternal as the gods themselves are. Nevertheless, the eternity of the Empire passes through instruments of violence against the peoples subjugated in the present. Thus, the cross and the Roman legion will become symbols in the social imaginary of the Palestine’s peasants. Imaginary that is constructed from images present in the daily routine. Crosses and soldiers were present in the Palestinian scenario to remind any peasants of their vulnerability and at the same time to reaffirm the perennity of an empire deified by force.